2001
DOI: 10.1097/00007632-200109010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Using Cineradiography for Continuous Dynamic-Motion Analysis of the Lumbar Spine

Abstract: Motion analyses using cineradiography helped to explain the phenomena of lumbar spine kinematics. Based on continuous dynamic-motion analysis with cineradiography, large f-e angle and disordered motion pattern during the flexion-backward course in the DS group I was considered to be caused by segmental instability. The decreased translation and disordered motion pattern throughout the flexion course in the DS group II was considered to be caused by restabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 12 publications
3
52
0
Order By: Relevance
“…Takayanagi [12] studied the motion patterns in asymptomatic volunteers and symptomatic patients with L4-5 DS in sitting postures and found that lumbar spine with DS presented disordered motion patterns and segmental instability. Okawa [13] reported that patients with DS showed disordered motion patterns while subject bent forward from a standing neutral position and then returned to the original position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takayanagi [12] studied the motion patterns in asymptomatic volunteers and symptomatic patients with L4-5 DS in sitting postures and found that lumbar spine with DS presented disordered motion patterns and segmental instability. Okawa [13] reported that patients with DS showed disordered motion patterns while subject bent forward from a standing neutral position and then returned to the original position.…”
Section: Discussionmentioning
confidence: 99%
“…Due to slippage, kinematics of the vertebrae with DS is altered, which may lead to a series of pathological processes and clinical symptoms. To reveal pathogenesis, explain clinical symptoms and decide treatment methods, kinematics of DS has been studied using a variety of techniques including lateral flexion-extension radiographs [10], biplanar radiographs [11], cineradiography [12,13], open MRI [14,15] and, etc. However, most of these studies focused on the anterior-posterior motion of the vertebral bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic studies may include plain radiographs, magnetic resonance imaging (MRI), computed tomography, and provocative discography 1,3,4,10,16,17,20,22,25,27) . Unfortunately, there is poor correlation between the presence of low back pain and imaging study findings in the general population 16,17,21) .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is poor correlation between the presence of low back pain and imaging study findings in the general population 16,17,21) . Numerous studies have documented that a high percentage of asymptomatic patients have abnormal findings on imaging studies of the presence of DDD 3,4,10,16,17,21,27) . Consequently, the decision to undertake surgical management of DDD requires extensive radiographic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile modulus and Poisson's ratio of the anulus fibrosus are likewise reduced [4]. As a result, anulus fibrosus fibers fail at lower loads leading to further degeneration [5] and abnormal spinal motion [6][7][8]. Although the course of disc degeneration cannot be predictably altered many investigators are seeking ways to enhance disc physiology and retard or reverse degeneration.…”
Section: Introductionmentioning
confidence: 99%